Penyusunan Model Enterprise Arsitektur Data, Aplikasi, dan Infrastruktur Teknologi Layanan IT Support Perguruan Tinggi Menggunakan Metode Enterprise Architecture Planning (EAP) - Renita Fauziah Samodra; Yudha Saintika; Dwi Mustika Kusumawardani (JASIEK (Jurnal Aplikasi Sains, Informasi, Elektronika dan Komputer), 2023)
Enterprise Architecture (EA) is an enterprise architecture modeling to assist management in managing utilization and development of Information Systems/Information Technology (IS/IT). ITTP in the utilization and development of IS/IT to fulfill its academic services, there is an Information Systems and Technology (STI) unit as the manager of service utilization and development. The problem with the STI ITTP service unit is that there is no IS/IT enterprise architecture model to support the development of its services. The solution to this problem requires an information and communication technology enterprise architecture model covering business processes, data, applications and technology infrastructure to be more organized using the Enterprise Architecture Planning (EAP) method. The results of this study are compiling the Architectural matrix that exists in the ITTP STI unit services in the form of business processes, data, applications and technology infrastructure, with research material data obtained from interviews and observations on the ITTP STI unit. The preparation of the matrix can later help the quality of the role of managing the utilization and development of IS/IT as expected by the STI ITTP unit.